DEVELOPMENT OF QR-CODE BASED DIGITAL COMICS MULTIMEDIA IN MADRASAH IBTIDAIYAH - Muhammad Syahru Romadhon,; Aristhalia Hevi Febrianti,; Chofifah Dwi Aprilia,; Samsul Susilawati, (AULADUNA: Jurnal Pendidikan Dasar Islam, 2025)
This study aims to develop QR-code-based digital comic multimedia as a learning media for IPAS on colonialism struggle topics in grade VI madrasah ibtidaiyah. The R&D method utilized the Lee & Owens model, encompassed analysis, design, development, implementation, and evaluation stages. Research instruments included: (1) teacher observation and interview sheets, (2) expert validation sheets, (3) student response questionnaires, and (4) learning outcome tests. Analysis results showed low use of technology-based media in primary schools. The product features interactive digital comics equipped with QR codes that allow access to videos and additional resources. The validation results demonstrate that the developed media is highly appropriate for use and has been proven effective in enhancing student learning outcomes. This media is interesting, interactive, and capable of fostering a spirit of nationalism in students. Development of QR-code-based digital comics can serve as an alternative innovation in IPAS learning, supporting digital transformation in madrasah ibtidaiyah.